Cumplimiento de los estándares de enfermería en pacientes con preclamsia severa en las áreas de alto riesgo obstétrico en el Hospital Gineco Obstétrico Luz Elena Arismendi en el primer semestre del 2017 - Cifuentes Tumaille, Jéssica Jacqueline (2017)
Preeclampsia is defined as one of the most common complications in pregnancy, its prevalence is 1.8 percent - 16.7 percent; In Ecuador was classified as the second cause of maternal death (INEC 2016) as it is one of the main causes of morbidity and mortality, this pathology is considered as a complication of maternal and fetal deaths. The main objective of this research project was to evaluate the fulfillment of nursing care in pregnant patients with severe preeclampsia hospitalized in the areas of high obstetric risk of the Obstetrical Gynecological Hospital Luz Elena Arismendi. The methodological design of this study is descriptive and prospective, using for data collection an observation guide and a questionnaire to measure the level of knowledge of the personnel involved. The study population consisted of 52 nurses from the areas of obstetric, hospitalization and emergency centers. The results of the study revealed a high level of knowledge in the personnel of the hospitalization area and an average knowledge in the areas of obstetric center and emergencies. Thus, it was also possible to verify a high compliance of nursing care standards in all areas, which were organized and protocolled to be evaluated. This project aims to provide new knowledge and parameters for nursing staff, which will strengthen nursing care in quality and warmth, and thus generate a high index of scientific knowledge in these professionals.